If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(z + -2) = 3 Reorder the terms: -6(-2 + z) = 3 (-2 * -6 + z * -6) = 3 (12 + -6z) = 3 Solving 12 + -6z = 3 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -6z = 3 + -12 Combine like terms: 12 + -12 = 0 0 + -6z = 3 + -12 -6z = 3 + -12 Combine like terms: 3 + -12 = -9 -6z = -9 Divide each side by '-6'. z = 1.5 Simplifying z = 1.5
| 17+(-3x)=14 | | 2x-10-7x=3(x-6) | | 6(7-6n)=114 | | 7(5x-4)=5+2x | | n^2+(-3)(4)=28 | | 17+(-3)=14 | | 5+X=-36 | | 2y+7=35 | | h=16t^2+52t+16 | | 4.95+11.95=64.70 | | 40+2m=-8(m+5) | | x+74+36=77 | | 5(x-3)-4(x-3)=3(x-1) | | 2x^4-10x^2+5=0 | | 10t^2-17t+6=0 | | -4w+8=-8(w+3) | | 0.23*50=1*x | | -4z=126 | | 3x-10(x+2)=1.22-7x | | 8x-1=-9+7x | | 3x+2x+8=7x-2 | | 5y=15y-90 | | x+38+90+x+68=180 | | -6(-1-6b)=-138 | | 4(x+6)=y-2 | | -8v+6(10+6v)=-10(v-7)-7(v+2) | | -3(x-4)+5=14 | | 3s-6=10+3s | | 16(x+1)-1=14(x+1) | | 4x=3(y+3) | | x+59+50=80 | | 2x^2-8=15x |